IDENTIFICATION OF BACTERIA ASSOCIATED WITH LOWER RESPIRATORY TRACT AMONG PATIENTS ATTENDING IN GENERAL HOSPITAL DR. PIRNGADI MEDAN - Naldi, Jefri; Rosidah, Rosidah; Loesnihari, Ricke (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The aim of this study was to establish cases of bacteria associated with lower respiratory tract infections (LRTIs) in General Hospital Dr. Pirngadi Medan with the view to identify the bacteria well as to assess their antibiotics susceptibility. Methods: An observation and prospective study were analyzed to patients with lower respiratory tract infection in respiratory and internal wards Dr. Pirngadi Hospital Medan. For the identification method of bacteria was using optochin test, catalase test, Mannitol salt agar, coagulase, indole, methyl red, Voges–Proskauer test, citrate, urease, and Triple Sugar Iron test. Results: The bacteria that cause lower respiratory tract infection were Pseudomonas aeruginosa (25.53%), Klebsiella pneumoniae (17.02%), Proteus sp. (14.89%), Staphylococcus aureus (12.77%), Escherichia coli (10.64%), Streptococcus pneumoniae (10.64%), and Haemophilus influenzae (8.51%). The result of sensitivity testing showed that gentamicin is more sensitive and the resistant antibiotic is chloramphenicol among all the tested antibiotics. Conclusion: P. aeruginosa was the most common isolated from LRTIs patients with gentamicin is the most sensitive antibiotics while chloramphenicol is the most resistant antibiotics among all the tested antibiotics.